THE INFLUENCE OF KNOWLEDGE AND ATTITUDES ABOUT FLOOD DISASTERS ON THE PREPAREDNESS OF STUDENTS IN PUBLIC HIGH SCHOOLS IN EAST JAKARTA - Septiyana, Anis; Rohmat, Dede; Waluya, Bagja (Sosio-Didaktika: Social Science Education Journal, 2025)
Flooding is one of the natural disasters that often hit East Jakarta City. In the context of disaster preparedness, students' knowledge and attitude are very important. This study aims to identify the influence of students' knowledge on flood preparedness in public high schools in East Jakarta City. In addition, this study also wants to explore the influence of learners' attitudes on disaster preparedness, and analyze the relationship between knowledge and attitudes in the context of preparedness. In this study, cluster random sampling technique was used with a total of 311 students. Data collection methods included observation, tests, questionnaires, interviews, and documentation studies. To analyze the data, various techniques were used, including testing of research instruments, prerequisite analysis, multiple linear regression analysis, and hypothesis testing. The results showed that the knowledge about flooding possessed by public high school students in East Jakarta City can be categorized as high, reaching 82%. This includes understanding, application, analysis and evaluation. Meanwhile, students' attitudes in dealing with flood disasters are in the medium category, at 76%, with components of accepting, responding, appreciating, and being responsible. Learners' preparedness is also in the moderate category with a percentage of 70%, which includes disaster risk knowledge, emergency response plans, disaster warning systems, and resource mobilization. From the analysis of the coefficient of determination (R²), an R² value of 0.544 was obtained. This shows that knowledge and attitude have an influence of 54.4% on disaster preparedness.